A measure of limited joint motion and deformity correlates with HLA-DRB1 and DQB1 alleles in patients with rheumatoid arthritis. Issue 11 (1st November 1999) - Cranney, Ann; Goldstein, Rose; Pham, Ba'; Newkirk, Marianna M; Karsh, Jacob
Abstract : OBJECTIVE: To assess factors associated with a poor outcome in rheumatoid arthritis (RA), a measure was developed of limited joint motion and deformity, a deformity index (DI), and correlated biochemical and genetic variables with the magnitude of the DI. METHODS: Forty patients were evaluated in a cross sectional study. Clinical measures included the DI and Health Assessment Questionnaire, and disease variables included the erythrocyte sedimentation rate, C reactive protein, rheumatoid factor, and HLA-DRB1 and DQB1 alleles. RESULTS: Significant correlations were noted between increasing DI and duration of RA and concentration of C reactive protein. Patients with a DQB1*301 allele or DR4 allele had a higher DI than those without, and a positive trend was noted between increasing DI and dose of DRB1 RA susceptibility alleles. The trend was lost when a non-linear regression technique was used to remove the effect attributable to C reactive protein, suggesting an interrelation between persistent inflammation and genetics in determining total joint damage. CONCLUSIONS: The DI may be useful to study interactions between genetic and inflammatory processes in rheumatoid disease progression.